A prospective study of uroflowmetry in 100 patients with lower urinary tract symptoms - Gohil, Vikram B.; Vyas, Adhish V.; Kinjal K., Dodiya (International Surgery Journal, 2019)
Background: Uroflowmetry is diagnostic procedure of various urinary tract diseases like urethral stricture, benign prostatic hyperplasia, neurogenic bladder, detrusor muscle overactivity by calculating the rate of urine expulsion against the time unit in second. Uroflowmetry is simple and non-invasive diagnostic method. Methods: This is a prospective study of 100 cases which fulfil inclusion and exclusion criteria. After taking informed written consent of the patients, they have gone under uroflowmetry study by Urocap 3 uroflowmeter, and graphs were obtained and result analysed. Results: Maximum number of patients has prolonged curve graph were diagnosed as benign prostate hypertrophy (BPH) (53%), dysfunctional voiding curve for detrusor overactivity (20%) intermittent flow curve for neurogenic bladder (7%), Box variety for urethral stricture (7%). Conclusions: In present study we found that uroflowmetry is helpful in diagnosis of certain urological pathologies. Common lower urinary symptoms were burning micturition, frequency and difficulty in micturition. Age group from 50-70 years was often presented with bladder outflow obstruction. Uroflowmetry overall useful in diagnosis of BPH and urethral stricture which can be supported by ultrasonography of prostate with PVRV and RGU respectively to avoid other invasive and more difficult pressure or flow urodynamic study.